Waffle‐inspired hydrogel‐based macrodevice for spatially controlled distribution of encapsulated therapeutic microtissues and pro‐angiogenic endothelial cells - Chi H. L. Pham; Yicong Zuo; Yang Chen; Nam M. Tran; Dang T. Nguyen; Tram T. Dang (Wiley, 2023)
Abstract Macro‐encapsulation systems for delivery of cellular therapeutics in diabetes treatment offer major advantages such as device retrievability and high cell packing density. However, microtissue aggregation and absence of vasculature have been implicated in the inadequate transfer of nutrients and oxygen to the transplanted cellular grafts. Herein, we develop a hydrogel‐based macrodevice to encapsulate therapeutic microtissues positioned in homogeneous spatial distribution to mitigate their aggregation while concurrently supporting an organized intra‐device network of vascular‐inductive cells. Termed Waffle‐inspired Interlocking Macro‐encapsulation (WIM) device, this platform comprises two modules with complementary topography features that fit together in a lock‐and‐key configuration. The waffle‐inspired grid‐like micropattern of the "lock" component effectively entraps insulin‐secreting microtissues in controlled locations while the interlocking design places them in a co‐planar spatial arrangement with close proximity to vascular‐inductive cells. The WIM device co‐laden with INS‐1E microtissues and human umbilical vascular endothelial cells (HUVECs) maintains desirable cellular viability in vitro with the encapsulated microtissues retaining their glucose‐responsive insulin secretion while embedded HUVECs express pro‐angiogenic markers. Furthermore, a subcutaneously implanted alginate‐coated WIM device encapsulating primary rat islets achieves blood glucose control for 2 weeks in chemically induced diabetic mice. Overall, this macrodevice design lays foundation for a cell delivery platform, which has the potential to facilitate nutrients and oxygen transport to therapeutic grafts and thereby might lead to improved disease management outcome.